Emergence of a High-Risk Klebsiella michiganensis Clone Disseminating Carbapenemase Genes - Prah, Isaac; Nukui, Yoko; Yamaoka, Shoji; Saito, Ryoichi (Frontiers in Microbiology, 2022)
Klebsiella michiganensis is emerging as an important human pathogen of concern especially strains with plasmid-mediated carbapenemase genes. The IncX3-blaNDM-5 plasmid has been described as the primary vector for blaNDM-5 dissemination. However, whether strains with this plasmid have any competitive edge remain largely unexplored. We characterized a blaNDM-5-producing Klebsiella michiganensis strain (KO_408) from Japan and sought to understand the driving force behind the recent dissemination of IncX3-blaNDM-5 plasmids in different bacterial hosts. Antibiotic susceptibility testing, conjugation, and whole-genome sequencing were performed for KO_408, a clinical isolate recovered from a respiratory culture. Fitness, stability, and competitive assays were performed using the IncX3-blaNDM-5 plasmid, pKO_4-NDM-5. KO_408 was ascribed to a novel sequence type, ST256, and harbored resistance genes conforming to its MDR phenotype. The blaNDM-5 gene was localized on the 44.9 kb IncX3 plasmid (pKO_4-NDM-5), which was transferable in the conjugal assay. The acquisition of pKO_4-NDM-5 did not impose any fitness burden and showed high stability in the host cells. However, transformants with pKO_4-NDM-5 were outcompeted by their host cells and transconjugants with the IncX3-blaOXA-181 plasmid. The genetic environment of blaNDM-5 in pKO_4-NDM-5 has been previously described. pKO_4-NDM-5 showed a close phylogenetic distance with seven similar plasmids from China. KO_408 clustered with strains within the KoI phylogroup, which is closely associated with carbapenemase genes. This study highlights the emergence of a high-risk Klebsiella michiganensis clone harboring carbapenemase genes and affirms that the recent spread of IncX3-blaNDM-5 plasmids might be due to their low fitness cost and stability but not their competitive prowess.